Cross-sectional study evaluating data quality of the National Cancer Registration and Analysis Service (NCRAS) prostate cancer registry data using the Cluster randomised trial of PSA testing for Prostate cancer (CAP). Issue 11 (14th November 2017) - Merriel, Samuel William David; Turner, Emma L; Walsh, Eleanor; Young, Grace J; Metcalfe, Chris; Hounsome, Luke; Tudge, Isobel; Donovan, Jenny; Hamdy, Freddie; Neal, David; Martin, Richard M
Abstract : Objectives: To compare the completeness and agreement of prostate cancer data recorded by the National Cancer Registration and Analysis Service (NCRAS) with research-level data specifically abstracted from medical records from the Cluster randomised triAl of prostate specific antigen (PSA) testing for Prostate cancer (CAP) trial. Design: Cross-sectional comparison study. Participants: We included 1356 men from the CAP trial cohort who were linked to the NCRAS registry. Primary and secondary outcome measures: Completeness of prostate cancer data in NCRAS and CAP and agreement for tumour, node, metastases (TNM) stage (T1/T2; T3; T4/N1/M1) and Gleason grade (4–6; 7; 8–10), measured by differences in proportions and Cohen's kappa statistic. Data were also stratified by year and pre-2010 versus post-2010, when NCRAS reporting standards changed. Results: Compared with CAP, completeness was lower in NCRAS for Gleason grade (41.2% vs 76.7%, difference 35.5, 95% CI 32.1 to 39.0) and TNM stage (29.9% vs 67.6%, difference 37.6, 95% CI 34.1 to 41.1). NCRAS completeness for Gleason grade (pre-2010 vs post-2010 31.69% vs 64%; difference 32.31, 95% CI 26.76 to 37.87) and TNM stage (19.31% vs 55.50%; difference 36.19, 95% CI 30.72 to 41.67) improved over time. Agreement for Gleason grade was high (Cohen's kappa, κ=0.90, 95% CI 0.88 to 0.93), but lower for TNM stage (κ=0.41, 95% CI 0.37 to 0.51) overall. There was a trend towards improved agreement on Gleason grade, but not TNM stage, when comparing pre-2010 and post-2010 data. Conclusion: NCRAS case identification was very high; however, data on prostate cancer grade was less complete than CAP, and agreement for TNM stage was modest. Although the completeness of NCRAS data has improved since 2010, the higher completeness rate in CAP demonstrates that gains could potentially be achieved in routine registry data. This study's findings highlight a need for improved recording of stage and grade data in the source medical records.